How to draw dinosaurs and other prehistoric creatures - Bergin, Mark , 1961- (How to draw, 2007)
Learn how to draw a variety of dinosaurs, from the fearsome Tyrannosaurus to the giant sauropods, as well as the flying and marine reptiles that lived at the same time. This work includes background information on each animal. It encourages children to 'record from first-hand observation, experience and imagination, and explore ideas'.